1994
DOI: 10.1111/j.1476-5381.1994.tb14761.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of ETA receptors in the facilitation by endothelin‐1 of non‐adrenergic non‐cholinergic transmission in the rat urinary bladder

Abstract: 1 Endothelin-1 (ET-1; 3-10 nM) raised the tone of rat bladders bathed in buffer containing atropine (1 gtM) plus guanethidine (3.4 JAM). In addition, ET-1 potentiated, in a concentration-dependent fashion (1-10 nM), the contractions evoked by both transmural nerve stimulation and applications of exogenous adenosine 5'-triphosphate (ATP). 2 The threshold concentration of ET-1 required to facilitate non-adrenergic non-cholinergic (NANC) transmission and potentiate ATP-induced contractions, was about 10 fold lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 49 publications
(48 reference statements)
0
27
0
Order By: Relevance
“…The main role of ET A receptors in the contractile effects of ETs in the detrusor has been confirmed by several other investigators in animal as well as human bladders (Donoso et al, 1994;Latifpour et al, 1995;Okamoto-Koizumi et al, 1999;Calvert et al, 2002;Yoshida et al, 2003). In human detrusor, OkamotoKoizumi et al (1999), using isometric contraction experiments and RT-PCR, demonstrated that the ET-1-induced contractions were mediated mainly by the ET A receptor and not by the ET B receptor.…”
Section: Peripheral Targetsmentioning
confidence: 75%
“…The main role of ET A receptors in the contractile effects of ETs in the detrusor has been confirmed by several other investigators in animal as well as human bladders (Donoso et al, 1994;Latifpour et al, 1995;Okamoto-Koizumi et al, 1999;Calvert et al, 2002;Yoshida et al, 2003). In human detrusor, OkamotoKoizumi et al (1999), using isometric contraction experiments and RT-PCR, demonstrated that the ET-1-induced contractions were mediated mainly by the ET A receptor and not by the ET B receptor.…”
Section: Peripheral Targetsmentioning
confidence: 75%
“…88 The functional role of ETs in the detrusor has not been established. However, in the rat bladder, Donoso et al 89 found that ET-1 potentiated the contractions evoked by both transmural nerve stimulation (ACh and ATP) and applications of ATP at peptide concentrations 10-fold below those needed to produce an increase in bladder tone. Locally generated ET-1 may thus not only exert a direct contractile effect on the myocyte, but also indirectly increase the effects of other mediators that influence myogenic activity.…”
Section: Local Mediators Influencing Spontaneous Activitymentioning
confidence: 99%
“…These results confirmed mainly previous pharmacological observations demonstrating functional significance of ET-1 receptors. [4][5][6][7][8][11][12][13][14]16) …”
Section: Discussionmentioning
confidence: 99%
“…ET-1 receptors have been shown to be present in several non-vascular tissues such as the heart, kidney and bladder, [3][4][5][6][7][8][9][10] but the receptor properties such as the subtype distribution in these tissues have not been characterized simultaneously. Also, the receptor binding of ET-1 receptor antagonists has not been comparatively examined in different tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation